Research Trends and Dominant Theories in Sebelas Maret Business Review: Tren Penelitian dan Teori Dominan di Sebelas Maret Business Review - Penatari, Resi Intan; Sutopo, Bambang (Academia Open, 2024)
Background: Bibliometric analysis is vital for understanding research trends and scholarly impact. Sebelas Maret Business Review (SMBR), active since 2016, has published 99 articles, yet its academic contribution remains underexplored. Gap: Limited studies address SMBR’s research focus, theoretical frameworks, and practical implications. Aim: This study analyzes SMBR publications (2016–2023) to identify trends, dominant theories, and key variables. Results: Findings highlight Agency Theory and Signaling Theory as prevalent frameworks, with "work environment" (9 cases) as a key independent variable and "performance" (12 cases) as the dominant dependent variable. Trends show a focus on digital transformation and COVID-19 impacts. Novelty: Using VOSviewer, this study offers the first bibliometric mapping of SMBR, revealing thematic and collaborative networks. Implications: The analysis informs future research, emphasizing sustainability and AI in management, while aiding practitioners and policymakers in evidence-based decision-making. Highlights: Research Focus: SMBR primarily explores managerial behavior, transparency, and performance using dominant theories like Agency and Signaling. Key Variables: "Work environment" and "performance" are the most frequently analyzed variables, reflecting organizational efficiency priorities. Novel Contribution: First bibliometric mapping of SMBR using VOSviewer, revealing research trends and collaboration networks. Keywords: Bibliometric Analysis, Research Trends, SMBR